Exploring the use of Gibbs’ reflective model in enhancing in-service ESL teachers’ reflective writing - Hashim, Siti Noor Aneeis; Yaacob, Aizan; Suryani, Ina; Mohd Asraf, Ratnawati; Bahador, Zolkefli; Supian, Nadya (Arab World English Journal (AWEJ), 2023)
While the importance of reflective writing is widely acknowledged worldwide, the lack of exposure to systematic reflective models to enhance reflexivity is a major concern among in-service teachers in many developing countries. This paper presents a qualitative case study that aimed to explore the elements reflected by a group of English as a Second Language in-service teachers through their reflective writing. Specifically, it explored how the in-service teachers wrote reflections before Gibb’s reflective model was introduced to them as well as examined to what extent the systematic model managed to help them write better reflections. This study contributed to the body of knowledge on reflective writing among in-service teachers. Gibbs’ reflective model was introduced as a systematic framework to guide their reflective writing for eight weeks. Multiple methods such as semi-structured interviews, reflection logs and field notes were collected and thematically analysed. The findings indicated that the teachers managed to write better reflections on their teaching after using the model. The teachers reported that Gibb’s reflective model provided clearer guidelines for writing reflection, minimized difficulties in the evaluation and analysis of their teaching, and provided a space for thinking about their action plans. Gibbs’s reflective model can be used as a tool to enhance ESL teachers’ reflexivity and professional development. Keywords: English as a second language, Gibbs reflective model, in-service teachers, primary school, reflective writing